Study on Control of Wall Deflection in Earth Stepped-Twin Retaining Wall Using Anchor Method by means of Numerical Simulation - Kazuki Maehara; Akihiro Hamanaka; Takashi Sasaoka; Hideki Shimada; Seiya Sakuma (Advances in Civil Engineering)
The demand for specific earth retaining wall methods is increasing along with the advancement and overcrowding of underground space use such as the presence of adjacent structures in an urban area. To cope with this, the method named earth stepped-twin retaining wall is increasingly being applied. However, there is a concern about the workplace if the earth pressure causes a heaving and pressing phenomenon from both ends of the retaining wall in the earth stepped-twin retaining wall. Therefore, we proposed the application of an anchor method that contains the inner and outer walls by using numerical simulation. The effects of the difference in soil properties, the horizontal distance between the outer and inner walls, and the depth of the outer wall embedment on the anchor were investigated. The results of this study show that the wall deflection of the inner wall could improve by adopting the anchor support. Besides, it was found that the inner wall can be efficiently suppressed by adopting the hybrid system with anchors and struts according to the soil properties, horizontal distance, and the depth of the outer wall.